THE NATIONAL IDENTIFICATION AND THE PROCESESS OF GLOBALIZATION - Русул, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with the influences of the globalization processes on the regeneration of some features of national identifications.